Multicolor XUV above threshold ionization of Argon - Della Picca, Renata (2015)
Argon photo-electron spectra produced by short-pulse extreme ultraviolet radiation, and with particular emphasis on the two-photon absorption region, is analyzed theoretically. The electromagnetic pulse is modeled to resemble experimentally available pulses and is built from a range of high-harmonics from an 800 nm laser. The photo-electron spectra show a characteristic peak structure due to the absorption of different combinations of photons, where the relative peak intensity is very sensitive to both the XUV pulse parameters and the target description. The theoretical result is further compared with experimental data, and good qualitative agreement is found.